Procedural sedation in pediatric dentistry: a narrative review - Gao, Feng; Wu, Yujia (Frontiers in Medicine, 2023)
Procedural sedation and analgesia are now considered standard care for managing pain and anxiety in pediatric dental patients undergoing diagnostic and therapeutic procedures outside of the operating room. Anxiolysis, which combines both pharmacologic and non-pharmacologic approaches, plays a significant role in procedural sedation. Non-pharmacologic interventions such as Behavior Management Technology can help reduce preprocedural agitation, ease the transition to sedation, reduce the required amount of medication for effective sedation, and decrease the occurrence of adverse events. As the introduction of novel sedative regimen and methods in pediatric dentistry, the potential role of mainstay sedatives administered by new routes, for new indications, and with new delivery techniques, should be considered. The purpose of this paper is to examine and discuss the current state of sedation techniques in pediatric dentistry.